An introduction to early modern English - Nevalainen, Terttu (Edinburgh textbooks on the English language., 2006)
An introduction to Early Modern English, this book helps students of English and linguistics to place the language of the period 1500-1700 in its historical context as a language with a common core but also as one which varies across time, regionally and socially, and according to register. The volume focuses on the structure of what contemporaries called the General Dialect - its spelling, vocabulary, grammar and pronunciation - and on its dialectal origins. The book also discusses the language situation and linguistic anxieties in England at a time when Latin exerted a strong influence on the rising standard language. The volume includes: The major changes in English from the 15th to the 18th century Emphasis on long-term linguistic developments Sources for the study of Early Modern English Illustrations ranging from drama and personal letters to trials and early science Exercises encouraging further exploration of the changing English language.